Determining the optimal distribution of bee colony locations to avoid overpopulation using mixed integer programming - Esteves, Ramon Joseph P. (Journal of Nature Studies, 2010)
This paper aims to find the best location of bee colonies in a certain area in such a way that each colony will have enough food resources. Mixed Integer Programming, which is already an established tool in optimization, is used to achieve the said goal. The output of this paper is a general model that determines the optimal distribution of bee colonies for any size and orientation of a field with diverse kinds of plants. As a prototype example, the best relocation of Trigona biroi colonies in a small community is determined.